Frontière intérieure et front pionnier - Anne Péné-Annette (Confins)
The Guiana of Venezuela, western part of the Guyana plateau, has the dual function of internal and international border. It developed as part of a regional development project, characterized as a pioneering mining and industrial front. This development has favoured border opening and the emergence of cross-border dynamics, through transport networks. The serious economic crisis in Venezuela is accelerating an economic decline and accentuating the disorganization in these border areas.